Study On Stroke In Young Patient Due To Cardiac Disease in Tertiary Care Hospital in Dhaka City (Journal of Medicine, 2016)
Objectives: Study of the risk factors associated with stoke due to cardiac disease in age group between 18 to 45 years of age,evaluate the risk factor of hospitalized stroke patients & to search for cardiac disease associated with stroke also appropriate preventive measure applicable for our country.Materials & Methods: Non randomized prospective observational study was carried out in the department of Neurology, Medicine & Cardiology unit of Dhaka Medical College Hospital between the periods of July 2009 to December 2009. Fifty (50) consecutive indoor patients more than 18 years of both sex admitted with suspicion of stroke. Diagnosis of stroke will be made from details clinical history clinical examination and confirmed by CT scan or MRI.Result: Fifty patients were randomly chosen for this study, of which 26 (52%) patients were male, 24 (48%) patients were female & male: female ratio was 1.08:1. Highest incidence of stroke was in between 3rd & 4th decade. The incidence of ischemic stroke 46 (92%) & hemorrhagic stroke 4(8%).Cardio embolism is the major (92%) risk factor for ischemic stroke. Among the cardiac risk factors, valvular disease (64%), MI (16%), &IHD (10%), Atrial fibrillation 8%, Patent foramen ovale 2%.Among the patients 33.33% of women with cerebral infarction were using OCP. Majority of the patients in this study were sedentary worker (45%). Among the stroke patients 8% & 10% had previous H/O stroke & TIA respectively.Conclusion: In this study a number of modifiable risk factors were identified, of which valvular heart disease & HTN are important risk factor next are DM & IHD smoking. Most of the valvular heart diseases are rheumatic in origin, which can be prevented through primary & secondary prevention of rheumatic fever.J MEDICINE July 2016; 17 (2) : 95-99